PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 013 TELUK PIYAI KECAMATAN KUBU - Jaroten Jaroten '; Zulkifli Zulkifli '; Lazim N Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The background of this research is the success of science learning isdetermined by how the teacher in planning. This study aims to determine whetherthere is any influence Cooperative learning model type two stay two stray bothindividually and classical to class IV student learning outcomes in sciencesubjects. Data were collected through observation using the observation sheet tothe data model of Cooperative Learning Type two stay two stray through UAS Iand UAS II for learning outcomes data. The results of the students increased inthe first cycle compared to prior to the action or before PTK, as for theimprovement of learning outcomes that occurred before and after the PTK heldthe first cycle increased. as for the improvement of learning outcomes thatoccurred before and after the cycle is held PTK increased the students whocompleted as many as 13 people from 20 students to 65% completeness. While inthe second cycle increasing student mastery as much as 85% or 17 people. Fromthe research and discussion as it has been described above that the use ofcooperative learning model TSTS correctly then the activity and student learningoutcomes be improved and better. This information proved that the hypothesiswhich says: the application of cooperative learning model to improve learningoutcomes TSTS IPA 013 fourth grade students of SDN Gulf Piyai Kubu district